Secondary cutaneous mucormycosis post-COVID-19: Case series from a tertiary center - B Abhirami; Prabhat Kumar; Dharmendra Kumar Mishra; Satyendra Prasad Yadav (Wolters Kluwer Medknow Publications, 2022)
Background: Mucormycosis is an angioinvasive mucorales fungal infection. Cutaneous type formed 10.5% of cases in India in precovid-19 era. Glucocorticoid-induced immunosuppression and hyperglycemia, reusable oxygen humidifiers in COVID-19 therapy, and preexisting uncontrolled diabetes mellitus contribute to post-COVID-19 mucormycosis. However, for post-COVID-19 cutaneous mucormycosis, sufficient data is not available. Aim: To study factors related to post-COVID-19 cutaneous mucormycosis. Methodology: Clinical and investigation details of six patients admitted in tertiary center with post-COVID-19 cutaneous mucormycosis. Results: Among six patients, three were males and three females; all in 45-60 years age group from districts under tertiary center. Site of eschar was face (four) and lips (two). All six were positive for COVID-19 10-12 days prior to admission for mucormycosis. All had intravenous steroids and supportive humidified oxygen therapy for minimum 1 week under COVID-19 treatment. They presented to emergency with ophthalmic/ENT complaints; subsequently, they developed cutaneous manifestations within 2-3 days. All six had diabetes mellitus, with above 400 mg/dL sugar levels at admission. Conclusion: This study's findings correlated with various studies across the country and elsewhere. Preexisting diabetes mellitus and steroid therapy for COVID-19 increase the risk of mucormycosis. Caution for early diagnosis, maintaining blood glucose levels, and judicious use of steroids for treatment of COVID-19 are indicated.